Perbandingan Keakuratan Metode Capital Asset Pricing Model dan Arbitrage Pricing Theory dalam Memprediksi Return Saham (Studi pada Perusahaan Sektor Barang Konsumsi dan Sektor Pertambangan yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) Peri - Yetti Afrida Indra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
CAPM is a balance model that can determine the risks and returns that investors will gain. Under the CAPM, the level of risk and the appropriate rate of return has a positive and linear relationship. The measure of risk that is an indicator affecting stock in CAPM is indicated by the variable β (beta). The bigger the β of a stock, the greater the risk it contains. This model links the expectation return rate of a risky asset with the risk of the asset in a balanced market condition. The population in this study is the stock price data of companies in the consumption sector and the mining sector listed on the Indonesia Sharia Sharia Index (ISSI) period 2013-2016. Based on the results of research and statistical tests, a more accurate model in predicting future ISSI stock returns is more accurate than the Arbitrage Pricing Theory (APT) model, because MADCAPM (0.0835) value MADAPT (0,5070). Furthermore, based on data processing with MannWhitney test shows that H0 is rejected, in the sense that there is a significant difference of accuracy between Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in predicting ISSI stock return. This is evidenced by the significance value (Sig) (0.002) smaller than (α) 0.05. Keywords: Comparison, Accuracy, Capital Asset Pricing Model (Capm), Arbitrage Pricing Theory (Apt), Stock Return.